“Determinación del ciclo biológico de podisus sp alimentado con larvas de musca doméstica en Laboratorio” - Sánchez Villacorta, Luz Dina (2007)
The present investigation was work developed in the Laboratory of Entomology of the National University of San Martin, located in Morales' district, located toan altitude of 350 m.s.n.m.m. andan annual precipitation of 1200 mm.; with the purpose of deterrnining the biology of the predator, when this is fed with larvas of domestic fly. To begin the investigation he/she was carried out the upbringing masal of Musca it tames used as prey for the upbringing of the pentatómido Podisus sp in laboratory. To know the biology of the predator he/she was carried out 1 a series of tests, each one with five repetitions with the purpose of obtaining real data of each one of the outlined biological parameters and evaluated, beginning with the included biological cycle the five stadiums ninfales and the period of incubation; the longevity of adults for sex; the reproductive capacity expressed in number of masses of eggs by female; total number of eggs for female; number of eggs for posture; pre-sexual intercourse; effective sexual intercourse; pre-oviposición; effective oviposición; percentage of viability of the eggs; survival; predación behavior and registration of the temperatura and Mumiciity relative maxim and mínimum of the laboratory. The obtained results are significant in comparison to other carried out studies of upbringing masal of Podisus sp, ALVAREZ, shows a smaller biological cycle to the one obtained, capacity reproductiva mínimum, smaller posture capacity as for the number of masses and bigger number of total eggs and average of eggs for mass, the sexual maturity allowed us to determine the precocity of the species Podisus in study; as well as a high predación capacity in their different immature stadiums and adult. Completing with a high percentage of viability of the eggs. These data allow to think about the use of the biological control, to maintain in balance the population of the worm cogolllero and of sorne lepidopterons at a level that doesn't produce economic damage and potenciar the population of the native predator, diminished by the indiscriminate use of lethal toxic pesticides for the ecology and the human health through the upbringing masal in the laboratory and their liberation in the field in concordant levels to the incidence of the plague, we can also transport this predator to other areas considering their average of survival of each stadium. At the end of the investigation it has been possible to complete the objectives outlined in this experiment satisfactorily, with the standardization of the technique of upbringing masal of the predator.